Integrated Business Model – Technology (IBM-T) practices: Bursa Malaysia Sector-Based Trends - Baharudin, Dayana Mastura; Marimuthu, Maran; Ibrahim, Haslindar; Jan, Amin; Adeneye, Yusuf Babatunde; Hamzah, Hana Halini; Zulkefli, Mohd Ikhwan Izzat; Ibrahim, Normardhiah (Business Management and Strategy, 2022)
Purpose – This study investigates the impact of the five main determinants of strengthening the Integrated Business Model – Technology (IBM-T) practices of the top 100 Malaysian Public Listed Companies (PLCs) through the Integrated Business Model – Technology components, moderated by the presence of the Women Board of Directors, Independent Board of Directors, and the Integrated Reporting 8 Content Elements study across the top 100 Malaysian PLCs. Design/methodology/approach – The methodology employed includes the purposive sampling method followed by descriptive statistics, content analysis, frequency of disclosures trend analysis and the One-Way ANOVA analysis derived from the Malaysian Code of Corporate Governance 2012 (MCCG 2012) and the Malaysian Code of Corporate Governance 2017 (MCCG 2017) together with previous studies of the analysis of the annual reports and integrated reports in order to explore the reporting of the Integrated Business Model - Technology, Women Board of Directors, Independent Board of Directors and the Integrated Reporting 8-Content Elements. Originality/value – This study is a systematic review of recent research developments in the Integrated Reporting, Business Model, MCCG 2012 and MCCG 2017. The Integrated Business Model - Technology, Women Board of Directors, Independent Board of Directors, and the Integrated Reporting 8-Content Elements scoring indices designed which could also be applied to other PLCs other than the Malaysian PLCs.